(untitled) (The Review of Diabetic Studies, 2022)
1,5-anhydroglucitol (1,5-AG) is a biomarker of acute hyperglycemia in diabetology and also in cardiodiabetology. It is used to monitor fluctuating glucose levels. 1,5-AG is a monosaccharide that is biochemically similar to D-glucose and originates from the nutrition. The presence of 1,5-AG in blood and tissue is nearly constant due to reabsorption in the renal proximal tubule. In acute hyperglycemia, renal reabsorption is inhibited by glucose and 1,5- AG is excreted in the urine, while its serum level decreases rapidly. 1,5-AG reflects glucose excursions over 1-3 days to 2 weeks. In this regard, low levels of serum 1,5-AG can be a clinical marker of shortterm glycemic derangements such as postprandial hyperglycemia, which is an important risk factor for the pathogenesis of coronary artery disease (CAD) as low levels of 1,5-AG reflect severe plaque calcification in CAD and correlate with high-density lipoprotein cholesterol (HDL-C) levels. For these reasons, 1,5-AG may also be a marker for atherosclerosis; in fact an even better marker than HbA1c or fructosamine which are normally used. 1,5-AG may also be a predictor of cardiovascular disease, left ventricular dysfunction after acute coronary syndrome (ACS), and mortality after ACS. This articles reviews the current knowledge on 1,5-AG related to its use as predictor for cardiovascular events.